Examining the Role of Attention and Instruction in At-Risk Kindergarteners: Electrophysiological Measures of Selective Auditory Attention Before and After an Early Literacy Intervention. (January 2013) - Stevens, Courtney; Harn, Beth; Chard, David J.; Currin, Jeff; Parisi, Danielle; Neville, Helen
Several studies report that adults and adolescents with reading disabilities also experience difficulties with selective attention. In the present study, event-related brain potentials (ERPs) were used to examine the neural mechanisms of selective attention in kindergarten children at risk for reading disabilities (AR group, n = 8) or on track in early literacy skills (OT group, n = 6) across the first semester of kindergarten. The AR group also received supplemental instruction with the Early Reading Intervention (ERI). Following ERI, the AR group demonstrated improved skills on standardized early literacy measures such that there were no significant differences between the AR and OT groups at posttest or winter follow-up. Analysis of the ERP data revealed that at the start of kindergarten, the AR group displayed reduced effects of attention on sensorineural processing compared to the OT group. Following intervention, this difference between groups disappeared, with the AR group only showing improvements in the effect of attention on sensorineural processing. These data indicate that the neural mechanisms of selective attention are atypical in kindergarten children at risk for reading failure but can be improved by effective reading interventions.